ADVANCING PALLIATIVE CARE IN THE UGANDA HEALTH SYSTEM: AN EVIDENCE-BASED POLICY BRIEF. (30th March 2015) - Nabudere, Harriet; Obuku, Ekwaro; Lamorde, Mohammed
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: This paper describes the development and findings for a policy brief on "Advancing the Integration of Palliative Care into the National Health System" and the subsequent use of this report. Methods: Key stakeholders involved with palliative care helped identify the problem and potential policy solutions to scale up these services within the health system. A working group of national stakeholder representatives and external reviewers commented on and contributed to successive drafts of the report. Research describing the problem, policy options and implementation considerations was identified by reviewing government documents, routinely collected data, electronic literature searches, contact with key informants, and reviewing the reference lists of relevant documents that were retrieved. Results: The palliative burden is not only high but increasing due to the rise in population and life expectancy. A few options for holistic, supportive care include: Home-based care increases chances of a peaceful death for the terminally ill surrounded by their loved ones; supporting informal caregivers improves their quality of life and discharge planning reduces unscheduled admissions and has the potential to free up capacity for acute care services. A combination of strategies is needed to effectively implement the proposed options as discussed further in this article. Conclusions: The policy brief report was used as a background document for two stakeholder dialogues whose main outcome was that a comprehensive national palliative care policy should be instituted to include all the options, which need to be integrated within the public health system. A draft policy is now in process.